Effects of inhaled ginger aromatherapy on chemotherapy-induced nausea and vomiting and health-related quality of life in women with breast cancer - Lua, Pei Lin; Salihah, Zakaria; Mamat, Nik Mazlan (Elsevier, 2015)
Objective: To assess the efficacy of inhaled ginger aromatherapy on nausea, vomiting and health-related quality of life (HRQoL) in chemotherapy breast cancer patients.Design: Single-blind, controlled, randomized cross-over study. Patients received 5-day aromatherapy treatment using either ginger essential oil or fragrance-matched artificial placebo(ginger fragrance oil) which was instilled in a necklace in an order dictated by the treatment group sequence.Setting: Two oncology clinics in the East Coast of Peninsular Malaysia.Main outcome measures: VAS nausea score, frequency of vomiting and HRQoL profile (EORTCQLQ-C30 scores).Results: Sixty female patients completed the study (age = 47.3 ± 9.26 years; Malay = 98.3%; on highly emetogenic chemotherapy = 86.7%). The VAS nausea score was significantly lower after ginger essential oil inhalation compared to placebo during acute phase (P = 0.040) but not sustained for overall treatment effect (treatment effect: F = 1.82, P = 0.183; time effect: F = 43.98,P < 0.001; treatment × time effect: F = 2.04; P = 0.102). Similarly, there was no significant effect of aromatherapy on vomiting [F(1, 58) = 0.29, P = 0.594]. However, a statistically significant change from baseline for global health status (P < 0.001) was detected after ginger essential oil inhalation. A clinically relevant 10 points improvement on role functioning (P = 0.002) and appetite loss (P < 0.001) were also documented while patients were on ginger essential oil. Conclusion: At present time, the evidence derived from this study is not sufficiently convincing that inhaled ginger aromatherapy is an effective complementary therapy for CINV. The findingsfor HRQoL were however encouraging with significant improvement in several domains.